19q13.33→qter trisomy in a girl with intellectual impairment and seizures - Carvalheira, Gianna (Meta Gene, 2014)
Rearrangements in chromosome 19 are rare. Among the 35 patients with partial 19q trisomy described, only six have a breakpoint defined by array. The 19q duplication results in a variable phenotype, including dysmorphisms, intellectual disability and seizure. In a female patient, although G-banding at 550 band-resolution was normal, multiplex ligation-dependent probe amplification (MLPA) technique and genomic array showed a 10.6 Mb terminal duplication of chromosome 19q13. Fluorescent in situ hybridization (FISH) revealed that the duplicated region was attached to the short arm of chromosome 21 and silver staining showed four small acrocentrics with nucleolar organization region (NOR) activity, suggesting that the breakpoint in chromosome 21 was at p13. This is the first de novo translocation between 19q13.33 and 21p13 described in liveborn. The chromosome 19 is known to be rich in coding and non-coding regions, and chromosomal rearrangements involving this chromosome are very harmful. Furthermore, the 19q13.33→qter region is dense in pseudogenes and microRNAs, which are potent regulators of gene expression. The trisomic level of this region may contribute to deregulation of global gene expression, and consequently, may lead to abnormal development on the carriers of these rearrangements.